Dukungan sosial teman sebaya dan resiliensi dengan stres akademik pada mahasiswa rantau tahun pertama - Alya Dwi Anggraeni; Diana Savitri Hidayati (Universitas Muhammadiyah Malang, 2024)
The number of universities in Java Island and the uneven quality of universities in Indonesia have resulted in the tendency of students to travel. Both academic and other adjustments, culture shock, communication difficulties can cause stress and anxiety. This also happens to first-year students who are in the stage of emerging adulthood where students will experience transitions that cause change and stress. Among the factors believed to impact academic stress levels are peer social support and resilience. The present study aimed to investigate the relationship between peer social support, resilience, and academic stress among first-year students from regional areas. The research sample consisted of 395 first-year undergraduate students (S1) from the University of Muhammadiyah Malang who originated from areas outside Greater Malang. Accidental sampling was employed as the sampling technique. The sampling technique uses accidental sampling. The research design used was correlational with spearman correlation analysis techniques and multiple correlations using SPSS 24. The results showed that the value of sig. F change of 0,142 > 0,05 means that there is no simultaneous or shared relationship between peer social support and resilience with academic stress. The implication of this study suggests that first-year regional students should actively maintain peer social support through frequent communication and engagement in campus activities to alleviate academic stress.